2021
DOI: 10.3390/pr10010080
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Processing: The Soft Spreadable Cheese Xygalo Siteias

Abstract: The aim of cheese manufacturers is to produce high quality and safe products. Along the food chain of “milk to cheese and food products”, milk is collected, transferred, and managed in a standardized manner; processing results in safe, ready-to-eat products, of high nutritional quality. Soft, acid cheeses are prepared in various regions of Greece, mainly from ewe milk, goat milk, or their mixtures. They are produced from the rennet and/or acid coagulation of thermally-treated, full-fat milk undergoing acidific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similarly, moisture content was also presented in soft creamy cheeses in the literature such as Tsalafouti (80.3%) in the Koutsoukis et al study [16], Galotyri cheese (76.9%) in the Samelis and Kakouri study [37], and Tvorog cheese (72.18%) in the Bonczar et al study [38]. According to research about spreadable cheeses by Kasapian et al [39], Danezis et al [22], and Lapidakis and Fragkiadakis [12], it was observed that the values of humidity are at high levels in all samples, which may be due to the high-heat treatment of the milk (87-90 • C) [40]. According to Giroux et al [41], the heat treatment of milk increases the recovery of protein in cheese due to the denaturation of whey proteins.…”
Section: Physicochemical Characteristics Of Tsalafouti Cheesementioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, moisture content was also presented in soft creamy cheeses in the literature such as Tsalafouti (80.3%) in the Koutsoukis et al study [16], Galotyri cheese (76.9%) in the Samelis and Kakouri study [37], and Tvorog cheese (72.18%) in the Bonczar et al study [38]. According to research about spreadable cheeses by Kasapian et al [39], Danezis et al [22], and Lapidakis and Fragkiadakis [12], it was observed that the values of humidity are at high levels in all samples, which may be due to the high-heat treatment of the milk (87-90 • C) [40]. According to Giroux et al [41], the heat treatment of milk increases the recovery of protein in cheese due to the denaturation of whey proteins.…”
Section: Physicochemical Characteristics Of Tsalafouti Cheesementioning
confidence: 81%
“…The most popular Greek varieties of acid-soft spreadable cheese for which there are published data are the following PDO cheeses: Galotyri, Katiki Domokou, Pichtogalo Chanion, Anevato, Kopanisti, and Xygalos of Sitia [11][12][13]. Galotyri is one of the oldest and most popular Greek acid spreadable cheeses traditionally produced with pasteurized milk at 90 • C, which is acidified naturally without starters in the regions of Epirus and Thessaly [13].…”
Section: Introductionmentioning
confidence: 99%